Répertoire de fleurons sur bandeaux de lampes Africaines type Hayes II - Bussière, Jean, (Archaeopress Publishing Ltd, 2015)
A comprehensive repertory of the stamps decorating the rims of Christian African lamps. This volume will be an indispensable tool to Mediterranean archaeologists for identifying even small fragments of lamps.